Progress and prospects in flexible tactile sensors - Liu, Ya-Feng; Wang, Wei; Chen, Xu-Fang (Frontiers in Bioengineering and Biotechnology, 2023)
Flexible tactile sensors have advantages of large deformation detection, high fault tolerance and excellent conformability, which enable conformal integration into complex surface of human skin for long-term bio-signal monitoring. The breakthrough of flexible tactile sensors rather than conventional tactile sensors greatly expand application scenarios. Flexible tactile sensors are applied in fields including not only intelligent wearable devices for gaming but also electronic skins, disease diagnosis devices, health monitoring devices, intelligent neck pillows, and intelligent massage devices in the medical field, intelligent bracelets and metaverse gloves in the consumer field, and even brain-computer interfaces. Therefore, it is necessary to provide an overview of the current technological level and future development of flexible tactile sensors to ease and expedite their deployment and to make the critical transition from laboratory to market. This paper discusses materials and preparation technologies of flexible tactile sensors, summarizing various applications in human signal monitoring, robotic tactile sensing and human-machine interaction. Finally, current challenges on flexible tactile sensors are also briefly discussed, providing some prospects for future directions.